Uji aktivitas afrodisiak ekstrak etanol daun cengkeh (Syzygium aromaticum L.) pada tikus putih jantan (Rattus norvegicus) - Patala, Recky; Risnawati, Risnawati; Wulandari , Ayu; Yanuarty , Rezky; Handayani , Tien Wahyu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Sex drive is what everyone needs to have a beautiful and harmonious sex life. Decreased sex drive is one of the factors that cause discord in relationships between men and women, and sexual dysfunction is a major concern. In Indonesia, this sexual disorder is most prevalent in men with a prevalence rate of 10% (all ages combined) and more than 50% occurs in the age group 50-70 years. The aim of this study was to determine the aphrodisiac effect of the extract by looking at several parameters, namely mount latency (ML), intromission frequency (IL), ejaculation latency (EL), mount frequency (MF), intromission frequency (IF), and ejaculation frequency (EF). This study used an experimental method with a post-test modified randomized control group design with 15 male white rats and 30 female white rats divided into 3 treatment groups with a ratio of (1: 2), each group consisting of 5 male rats and 10 female rats. Normal control group (NaCMC 0.5%), positive control group (X-Gra 52.5 mg/kgBB), and control test clove leaf extract sample at a dose of 250 mg/kgBB. Administration of extracts and comparators was only given to male white rats for 30 days. The results of this study indicate that clove leaf extract contains secondary metabolites of flavonoids, saponins, alkaloids, tannins, and strong antioxidants. The administration of clove leaf of extract at a dose of 250 mg/kg body weight showed a significant difference between the positive group and clove leaf of extract with a value of P < 0.05, this indicates that clove leaf of extract has aphrodisiac activity.